The changing academic profession: Towards empowering leadership in teaching. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)

(untitled)
Being part of a 22-country study on the changing academic profession (CAP project) which began in 2006, the research instrument (a questionnaire on the changing academic profession) was designed by the Method Group based at Kessel University, Germany which laid out sampling and data collection procedures. The Malaysia study used mailed or/and online questionnaires which were sent out to academics in both public and private higher education institutions. Data collection was completed in June 2007. A total of 1,176 completed questionnaires were analysed.